LncRNA MALAT1/microRNA-30b axis regulates macrophage polarization and function - Ahmad, Imran; Naqvi, Raza Ali; Valverde, Araceli; Naqvi, Afsar R. (Frontiers in Immunology, 2023)
Macrophages (Mφ) are long-lived myeloid cells that can polarize towards the proinflammatory M1 or proresolving M2 phenotype to control diverse biological processes such as inflammation, tissue damage, and regeneration. Noncoding RNA are a class of nonprotein-coding transcriptome with numerous interdependent biological roles; however, their functional interaction in the regulation of Mφ polarization and immune responses remain unclear. Here, we show antagonistic relationship between lncRNA (MALAT1) and microRNA (miR-30b) in shaping macrophage polarization and immune functions. MALAT1 expression displays a time-dependent induction during Mφ differentiation and, upon challenge with TLR4 agonist (E. coli LPS). MALAT1 knockdown promoted the expression of M2Mφ markers without affecting M1Mφ markers, suggesting that MALAT1 favors the M1 phenotype by suppressing M2 differentiation. Compared to the control, MALAT1 knockdown resulted in reduced antigen uptake and processing, bacterial phagocytosis, and bactericidal activity, strongly supporting its critical role in regulating innate immune functions in Mφ. Consistent with this, MALAT1 knockdown showed impaired cytokine secretion upon challenge with LPS. Importantly, MALAT1 exhibit an antagonistic expression pattern with all five members of the miR-30 family during M2 Mφ differentiation.Dual-luciferase assays validated a novel sequence on MALAT1 that interacts with miR-30b, a microRNA that promotes the M2 phenotype. Phagocytosis and antigen processing assays unequivocally demonstrated that MALAT1 and miR-30b are functionally antagonistic. Concurrent MALAT1 knockdown and miR-30b overexpression exhibited the most significant attenuation in both assays. In human subjects with periodontal disease and murine model of ligature-induced periodontitis, we observed higher levels of MALAT1, M1Mφ markers and downregulation of miR-30b expression in gingival tissues suggesting a pro-inflammatory function of MALAT1 in vivo. Overall, we unraveled the role of MALAT1 in Mφ polarization and delineated the underlying mechanism of its regulation by involving MALAT-1-driven miR-30b sequestration.